Enhancing Civil Servant Competency through Structural Position Equalization at the National Unity and Politics Department of Pasangkayu Regency, West Sulawesi Province - Ambarawati, Gusti Ayu; Hani, Abdurrachman; Dewi, Ayu Raditya Kencana (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
The current bureaucratic restructuring policy eliminates the Echelon III, IV, and V positions. The Ministry of State Officials Empowerment and Bureaucratic Reform (Kemenpan&RB) issued Circular Letter (SE) of the Minister of PAN and RB Number 393 of 2019, outlining Strategic and Concrete Steps to Simplify the Bureaucracy. Consequently, civil servants underwent competency adjustments following the transition from structural to functional positions at the National Unity and Politics Service in Pasangkayu Regency, West Sulawesi Province. These reforms, initiated in response to Indonesia's recent crises, have significantly bolstered the foundational aspects of democratic life in the country. To evaluate the competencies of civil servants post-transition, the author employed Gordon's (1988) competency theory, which encompasses dimensions such as knowledge, understanding, values, abilities, attitudes, and interests. The research employed a descriptive qualitative method to conduct evaluations, facilitating an in-depth analysis of the competencies of employees affected by the structural-to-functional position equalization at the National Unity and Politics Service in Pasangkayu Regency, West Sulawesi Province. Overall, the competencies of civil servants in the National Unity and Politics Department of Pasangkayu Regency have not yet reached optimal levels. Challenges such as inadequate budgetary support for competency development and insufficient readiness among civil servants following the equalization of positions continue to hinder efforts to enhance employee competency at the National Unity and Politics Service.